2017
DOI: 10.1016/j.bbadis.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Evening and morning peroxiredoxin-2 redox/oligomeric state changes in obstructive sleep apnea red blood cells: Correlation with polysomnographic and metabolic parameters

Abstract: We have examined the effects of Obstructive Sleep Apnea (OSA) on red blood cell (RBC) proteome variation at evening/morning day time to uncover new insights into OSA-induced RBC dysfunction that may lead to OSA manifestations. Dysregulated proteins mainly fall in the group of catalytic enzymes, stress response and redox regulators such as peroxiredoxin 2 (PRDX2). Validation assays confirmed that atmorning the monomeric/dimeric forms of PRDX2 were more overoxidized in OSA RBC compared to evening samples. Six mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Even though there are a multitude of studies investigating one or a few cardiac and inflammatory biomarkers in OSA, few other proteomic studies of adult OSA exist (Feliciano et al, 2017; Jurado‐Gamez et al, 2012; Kim et al, 2009; Seetho et al, 2014). In clinic‐based studies with male study populations, changes in the levels of proteins involved in lipid metabolism, vascular pathways, the complement system, oxidative stress and the acute phase response in association with OSA have been reported (Feliciano et al, 2017; Jurado‐Gamez et al, 2012; Kim et al, 2009). In a larger study investigating urinary proteomics in obese subjects, including both women and men, 24 proteins showed changed levels in OSA, but the differences did not reach significance after adjustment for multiple testing (Seetho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there are a multitude of studies investigating one or a few cardiac and inflammatory biomarkers in OSA, few other proteomic studies of adult OSA exist (Feliciano et al, 2017; Jurado‐Gamez et al, 2012; Kim et al, 2009; Seetho et al, 2014). In clinic‐based studies with male study populations, changes in the levels of proteins involved in lipid metabolism, vascular pathways, the complement system, oxidative stress and the acute phase response in association with OSA have been reported (Feliciano et al, 2017; Jurado‐Gamez et al, 2012; Kim et al, 2009). In a larger study investigating urinary proteomics in obese subjects, including both women and men, 24 proteins showed changed levels in OSA, but the differences did not reach significance after adjustment for multiple testing (Seetho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This has the potential to add to our understanding of underlying pathophysiological mechanisms linking sleep‐disordered breathing to cardiovascular disease, and to identify subpopulations of patients with OSA at risk of cardiovascular disease. There are a few clinic‐based studies of proteomics in OSA that have contributed important information on how OSA affects protein expression in serum (Jurado‐Gamez et al, 2012; Kim et al, 2009), red blood cells (Feliciano et al, 2017) and urine (Seetho et al, 2014). Most have only included men, while studies of women, larger community‐based studies, and studies of the effect of OSA during REM sleep on cardiac and inflammatory proteins are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly when protein oxidation patterns were studied in the morning in the RBCs of patients suffering from this condition, significantly higher oxidation of Prx2 was observed, to the extent that it is now considered a viable candidate biomarker for monitoring the severity and treatment of this pathological condition (37). This correlation does not hold true in invertebrates, though.…”
Section: Functions Of Catalytically Inactive Prxsmentioning
confidence: 99%
“…Dysfunction in RBC homeostasis has been described as a potential source of systemic inflammation that leads to metabolic and cardiovascular diseases such as those associated with OSA [12]. By two dimensional difference gel electrophoresis (2D-DIGE) proteomics, we demonstrated that OSA induces differential changes in RBC cytoplasmic proteome [10,11], in which redox-regulators such as peroxiredoxin-2 (PRDX2) are the most dysregulated. Since RBC is devoid of any translational machinery, these changes might result from post-translational modifications (PTM) regulation.…”
Section: Introductionmentioning
confidence: 96%
“…Our group has investigated for the first time to our knowledge the red blood cell (RBC) proteome from OSA patients to better understand the underlying mechanisms while uncovering potential biomarkers for a more cost-effective OSA diagnosis or as predictors of treatment [2,10,11]. Why RBCs?…”
Section: Introductionmentioning
confidence: 99%